2009
DOI: 10.3987/com-09-11812
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Optically Active P-Chirogenic Ferrocene-Fused Benzophosphole by Diastereoselective Intramolecular Cyclization of Phosphanylferrocene Derivatives

Abstract: A novel optically active P-chirogenic ferrocene-fused benzophosphole, (S Fc ,R P )-4-phenylbenzo[b]ferroceno[d]phosphole, was synthesized by diastereoselective intramolecular cyclization of (S Fc )-1-(diphenylphosphanyl)-2-(2-lithiophenyl)ferrocene intermediates in two routes. The geometry of the new P-chirogenic ferrocenophosphole including absolute configuration of the phosphorous was disclosed by single crystal X-ray analysis of the palladium complex derived from the reaction of the phosphole with di-μ-dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…Similar cyclizations of lithio-biphenylphosphines were also observed when the species was generated from halobiphenyl-2-ylphosphines through halogen–lithium exchange (Scheme 37 ). 53 54 Related studies have been reported by Kurita and co-workers, 55 Xiao and co-workers, 56 and Hayashi and co-workers. 57…”
Section: Construction Of a Phosphole Skeleton Using Aryl Compoundssupporting
confidence: 53%
“…Similar cyclizations of lithio-biphenylphosphines were also observed when the species was generated from halobiphenyl-2-ylphosphines through halogen–lithium exchange (Scheme 37 ). 53 54 Related studies have been reported by Kurita and co-workers, 55 Xiao and co-workers, 56 and Hayashi and co-workers. 57…”
Section: Construction Of a Phosphole Skeleton Using Aryl Compoundssupporting
confidence: 53%